Sodium nitrite impacts the peripheral control of contracting skeletal muscle microvascular oxygen pressure in healthy rats - Colburn, Trenton David (Kansas State University, 2016)
Exercise intolerance characteristic of diseases such as chronic heart failure (CHF) and diabetes is associated with reduced nitric oxide (NO) bioavailability from nitric oxide synthase (NOS), resulting in an impaired microvascular O₂ driving pressure (PO₂mv: O₂ delivery – O₂ utilization) and metabolic control. Infusions of the potent NO donor sodium nitroprusside augment NO bioavailability yet decrease mean arterial pressure (MAP) thereby reducing its potential efficacy for patient populations. To eliminate or reduce hypotensive sequellae NO₂⁻ was superfused onto the spinotrapezius muscle. It was hypothesized that local NO₂⁻ administration would elevate resting PO₂mv and slow PO₂mv kinetics (increased τ: time constant, MRT: mean response time) following the onset of muscle contractions. In 12 anesthetized male Sprague-Dawley rats, PO₂mv of the circulation-intact spinotrapezius muscle was measured by phosphorescence quenching during 180 s of electrically-induced twitch contractions (1 Hz) before and after superfusion of NaNO₂ (30 mM). NO₂⁻ superfusion elevated resting PO₂mv (CON: 28.4 ± 1.1 vs NO₂⁻: 31.6 ± 1.2 mmHg, P ≤ 0.05), τ (CON: 12.3 ± 1.2 vs NO₂⁻: 19.7 ± 2.2 s, P ≤ 0.05) and MRT (CON: 19.3 ± 1.9 vs NO₂⁻: 25.6 ± 3.3 s, P ≤ 0.05). Importantly, these effects occurred in the absence of any reduction in MAP (103 ± 4 vs 105 ± 4 mmHg, pre- and post-superfusion respectively; P ˃ 0.05). These results indicate that NO₂⁻ supplementation delivered to the muscle directly through NO₂⁻ superfusion enhances the blood-myocyte driving pressure of oxygen without compromising MAP at rest and following the onset of muscle contraction. This strategy has substantial clinical utility for a range of ischemic conditions.
Keywords: Nitric oxide; Microcirculation; Oxygen delivery; Vascular control; Beet root; Nitrate